Treatment of Complicated Hepatic Alveolar Echinococcosis Disease With Suspicious Lymph Node Remote Metastasis Near the Inferior Vena Cava-Abdominal Aorta: A Case Report and Literature Review - Xu, Xiaolei; Gao, Cancan; Qian, Xinye; Liu, Hong'en; Wang, Zhan; Zhou, Hu; Zhou, Ying; Wang, Haijiu; Hou, Lizhao; He, Shaoshuai; Feng, Xiaobin; Fan, Haining (Frontiers in Oncology, 2022)
Echinococcosis is a human-animal parasitic disease caused by Echinococcosis tapeworm larvae in humans. From a global perspective, it is mainly prevalent in the mid-high latitudes of the Northern Hemisphere, and it is a widespread infectious disease. Its form, host and release areas are slightly different. In clinical practice, Echinococcus granulosus (hepatic cystic echinococcosis) is the most common. Its growth mode is swelling growth and its metastasis is more common in implanted metastasis; However, hepatic alveolar echinococcosis (HAE) is rare. It has been reported that HAE can metastasize through the blood or lymph nodes, and its invasive growth pattern is known as “carcinoma”. At this time, it may be accompanied by invasion of the portal vein and inferior vena cava(IVC)or metastasis to distant organs outside the liver (such as lung, brain, lymph nodes). Most patients are in the middle or late stages, making treatment complicated. World Health Organization guidelines recommend radical resection of HAE; However, there is no consensus on lymph node dissection. To date, there have been no reports of cases of HAE accompanied by inferior vena cava-para-abdominal aortic suspected lymph node metastasis and infection. This article reports a clinical case of a complex HAE treated by the surgical method of “middle liver resection + abdominal enlarged lymph node resection + inferior vena cava repair”, and histological examination was performed to illustrate the differences in microscopic pathology of alveolar echinococcosis invading the liver and lymph nodes at different magnifications. This article reviews the relevant literature on HAE and derives the latest treatment methods for HAE to provide a reference for future clinical cases of similar alveolar echinococcosis and maximize the benefits of patients.